Adsorption of soft particles at fluid interfaces. Issue 37 (7th October 2015) - Style, Robert W.; Isa, Lucio; Dufresne, Eric R.
<x xml:space="preserve">Abstract</x> We explain why soft particles make good emulsifiers by analysing their deformations at a fluid–fluid interface.